Improving understanding of place value of numbers through the STAD type cooperative learning model and media stick box - Luviana, Rika; Irawati, Riana; Isrok'atun, Isrok'atun (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
The background of this research highlights that students often struggle to understand the place value of numbers, as each digit in a number represents a value based on its position. This challenge arises because the learning process lacks the use of engaging media and relies heavily on one-way interactions. To address this issue, a teaching approach that incorporates media and promotes active student involvement is required. This research implements the STAD-type cooperative learning model assisted by a stick box to enhance students' understanding of place value concepts. The study employs a quasi-experimental nonequivalent control group design method, with fifth-grade students from public elementary schools in North Sumedang District as the population. The primary research instrument is an essay test designed to measure conceptual understanding, supplemented by non-test instruments such as observations and questionnaires to collect additional data. The findings indicate that the STAD-type cooperative learning model assisted by a stick box significantly improves students' understanding of the place value concept, with a gain score of 0.746 categorized as high. In contrast, the conventional learning model resulted in a gain score of 0.178, categorized as low. Thus, it can be concluded that there is a significant difference in conceptual understanding of place value between students who learn using the STAD-type cooperative model with stick box assistance and those who engage in conventional learning methods.